Factors associated with the beginning of premature breastfeeding - Solís-Rojas, Mirian (2019)
Objective. To analyse the factors associated with the initiation of early breastfeeding of the National Mother Teaching Hospital "San Bartolomé", September to October 2017. Material and Methods. Observational, analytical, retrospective and cross-sectional study. We surveyed 191 women cases who started early and 191 controls. Regarding the analysis of the data, absolute and relative frequencies were estimated for the qualitative variables, and in the case of the quantitative variables, means and standard desviation were estimated; to find the association, the Chi-square test was used and Odds Ratio test. Results. Sociocultural factors, an association was found for student occupation, non-deformity of the breasts due to breastfeeding, the use of infusions to strengthen the stomach) with the on set of breastfeeding. Institutional results, an association was found between receiving information about breastfeeding in prenatal care, the delay in bringing the baby between 10 and 25 minutes and have a favorable environment for breastfeeding with the beginning of breastfeeding. No association was found between the obstetric factor, the neonatal factor and the beginning of early breastfeeding. Conclusion. The factors significantly associated with the start of early breastfeeding were: student occupation, .Know that non-deformity of the breasts, know that babies do not need to drink fusions, the time it takes to bring the baby from 10 to 25 minutes and have a favorable environment for breastfeeding.